2014
DOI: 10.1055/s-0034-1372244
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin versus Unfractionated Heparin during Percutaneous Coronary Intervention in Patients at High Risk for Bleeding

Abstract: The overall rate of bleeding complications during interventional therapeutic procedures for coronary heart disease by the femoral approach is 1.5 to 9%. 1 Although bleeding is considered a minor complication related to percutaneous coronary intervention (PCI), 2 on rare occasions, it might lead to life-threatening situations that must be treated by intensive medical or surgical approaches. 3 These events are multifactorial, involving patient-, physician-, and nursing staff-related prognosis-worsening factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Peri-procedural bleeding events, up to 50% arise from the access site, remain the most common non-cardiac complication following PCI and have been associated with significant morbidity, mortality, and financial burden to the healthcare system. These events are multifactorial and are associated with: (1) patient-related factors (female sex, age >70 years); (2) comorbidities such as diabetes mellitus, obesity, hypertension, and diseases inhibiting clot formation, such as uremia and thrombocytopenia; (3) and procedural factors (eg, port of access, mode of arterial puncture and anticoagulation regimen) [79] . Numerous randomized trials have demonstrated that major bleeding (both access site and non-access site) is less frequent in patients treated with bivalirudin [37,43,80,81] .…”
Section: Should Bivalirudin Use Be Reconsidered In Ppci?mentioning
confidence: 99%
See 1 more Smart Citation
“…Peri-procedural bleeding events, up to 50% arise from the access site, remain the most common non-cardiac complication following PCI and have been associated with significant morbidity, mortality, and financial burden to the healthcare system. These events are multifactorial and are associated with: (1) patient-related factors (female sex, age >70 years); (2) comorbidities such as diabetes mellitus, obesity, hypertension, and diseases inhibiting clot formation, such as uremia and thrombocytopenia; (3) and procedural factors (eg, port of access, mode of arterial puncture and anticoagulation regimen) [79] . Numerous randomized trials have demonstrated that major bleeding (both access site and non-access site) is less frequent in patients treated with bivalirudin [37,43,80,81] .…”
Section: Should Bivalirudin Use Be Reconsidered In Ppci?mentioning
confidence: 99%
“…(1) patient-related factors (female sex, age >70 years); (2) comorbidities such as diabetes mellitus, obesity, hypertension, and diseases inhibiting clot formation, such as uremia and thrombocytopenia; (3) and procedural factors (eg, port of access, mode of arterial puncture and anticoagulation regimen). [79] Numerous randomized trials have demonstrated that major bleeding (both access site and non-access site) is less frequent in patients treated with bivalirudin. [37,43,80,81] Thus, bivalirudin is recommended to reduce bleeding events in STEMI patients with a high risk of bleeding, especially those with multiple high-risk factors.…”
Section: Study Characteristics Designmentioning
confidence: 99%